Morphological Spectrum of Intracranial Space Occupying Lesions at Tertiary Care Hospital: A Clinicopathological Study - Soniya, Payal Jayprakash; Patel, Meena Avinash; Dixit, Shivani Harishankar; Goswami, Hansa (Annals of Pathology and Laboratory Medicine, 2024)
Background: An "Intracranial Space-Occupying Lesion" (ICSOL) is defined as a mass lesion in the cranial cavity with diverse etiology, such as benign or malignant neoplasm, inflammatory or parasitic lesion, hematoma, or arteriovenous malformation. Materials and Methods: Biopsies of 202 cases of intracranial space-occupying lesions were received in the Department of Pathology, B.J. Medical College, Ahmedabad, during the period of December 2022 to May 2023. All specimens were preserved in 10% formalin and allowed to fix for 24 hours. Paraffin-embedded sections of 5 microns were cut, and the Hematoxylin and Eosin-stained sections of the CNS lesions were studied. Results: Out of the total 202 cases, 176 were neoplastic lesions and 26 were non-neoplastic lesions. Among the 176 neoplastic intracranial tumors, 173 (98.3%) were primary, and 3 (1.7%) were metastatic. The most common type of intracranial tumor was Meningioma (33 cases, 18.6%), followed by Astrocytoma (31 cases, 17.5%). The most common age group affected by neoplastic lesions was 21-30 years, followed by the 31-50 years age group. The most common age group with non-neoplastic lesions was 31-40 years. Among the 26 cases of non-neoplastic intracranial lesions, 20 cases of cystic lesions and 6 cases of cerebral abscess were encountered. Conclusion: The surgical pathologist plays an important role in the accurate diagnosis of various intracranial space-occupying lesions, which is of immense help for patient prognosis and treatment [3]. Histopathological study remains the gold standard for the diagnosis and grading of tumors, on which clinicians can decide the further line of management.